Study on Students' Attitudes Toward Generative AI of Student at the People's Police Academy - LATTHACHANLA , Bounpheng; LOUANGVILAY, Xaythavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of the research were 1) to study the behavior of using generative AI of students at the People's Police Academy, 2) to study the acceptance of using generative AI of students at the People's Police Academy, and 3) to study the impacts and risks of using generative AI of students at the People's Police Academy. Using quantitative research methods, which used a questionnaire to ask for opinions from a sample group of 400 people, using the SPSS program to analyze data including frequency, percentage (%), mean (), and standard deviation (SD). The results found that: The behavior of using generative AI of students at the People's Police Academy: Used for information searching, accounting for 76%; used 2-3 times/day; prompts used are in Lao; the application used is ChatGPT, accounting for 82%. Opinions on the acceptance of using generative AI of students at the People's Police Academy at a "Good" level, such as generative AI helps reduce time in searching for information at a "Good" level ( =4.04, SD=67.53); increases work efficiency at a "Good" level (=3.87, SD=64.46); has many applications to choose at a "Good" level (=3.92, SD=64.92); and will have more development in the future at a "Good" level (=4.16, SD=74.74). Opinions on impacts and risks of using generative AI of students at the People's Police Academy: The analysis results showed average mean values, such as over-reliance and trust in AI at a "Moderate" level (=3.53, SD=52.68); AI may reduce human creativity at a "Moderate" level (=3.57, SD=53.14); lack of laws regulating safe AI use at a "Moderate" level (=3.70, SD=54.06); and AI can be used to create fake news or deceptive information at a "Good" level (=3.88, SD=57.04).